Ovarian cancer: avoiding compromising quality of life during intense chemotherapy sessions. Issue 4 (3rd July 2016) - Gibson, Steven J.; Clark, Jason A.; Chase, Dana M.
ABSTRACT: Introduction : In 2008, we published on the application of supportive care to ovarian cancer patients which involves caring for a patient's symptoms during and/or after treatment with an objective of providing these women with an improved quality of life (QoL). This complex, multi-dimensional field involves all body systems and collaboration among multiple medical specialties. Areas Covered : In this updated review, we have incorporated new data investigating QoL and supportive care in ovarian cancer, maintaining our format of analyzing the data by separating it into two categories: tumor-related and treatment-related morbidities. The main themes within these categories include nausea and vomiting, abdominal pain, anxiety and depression, fatigue and anemia, small bowel obstruction, sexual dysfunction, and peripheral neuropathy, to name a few. Expert Commentary : While all of these components are challenging to manage, the oncologist must act as a facilitator who either addresses these needs or send the patient to the appropriate healthcare provider who can address these issues. As we work to meet these supportive care needs, the aim is to improve QoL and with that, hopefully see improved survival outcomes in ovarian cancer patients.